Feminism and the Cooling of Intimacy. Unintended Consequences of Women’s Movements - Musiał, Maciej (ETHICS IN PROGRESS, 2013)
Numerous diagnoses of contemporary transformations of love and eroticism emphasise the fact that the intimate life has become democratised and liberated. Anthony Giddens argues that personal relationships increasingly become compatible with the model of pure relationship, which means that they are more egalitarian and that both partners are free to choose and to negotiate the shape of their relations. Jeffrey Weeks claims that in “the world that we have won”, women, homosexuals and queers are increasingly considered as equal to heterosexual men. Most scholars agree that feminism(together with gays’ and lesbians’ movements) is one of most important factors that enabled the democratisation of intimacy. Yet, it is possible to distinguish some interesting approaches that examine the unintended consequences of women’s emancipation. Sociologists like Arlie Russell Hochschild and Eva Illouz recognise the importance of feminism in democratising intimacy, thus they also claim that liberation of women has entailed rationalisation and commercialisation of intimacy. One of Hochschild’s main thesis is that feminism commercialises intimacy by legitimising “the commercial spirit of intimate life”. What is more, she argues that instead of humanizing men feminism is capitalising women. On the other hand, Illouz persuades that feminism – together with therapeutic discourse – rationalises intimacy by emphasising the necessity of analysing and quantifying all aspects of intimate life. Hochschild and Illouz claim that feminism unintentionally makes intimacy “cold” – that is that it suggests focusing on personal autonomy and perceiving warm and close bonds as an endangerment for that autonomy. The cooling entails loosening of family and intimate relationships and making individuals more attached to the market. In the end, both sociologists agree that “cool” branches of feminism make women similar to men and intimacy similar to the market